Gonadal hormones and metabolic syndrome in middle-aged and elderly males: results from a prospective cohort study in China - Zhang, Zhuo; Chen, Yingna; Li, Na; Huang, Chulin; Lin, Diaozhu; Wang, Chengzhi; Wang, Chunying; You, Lili; Li, Lingling; Li, Fangping; Liang, Ying; Xiao, Huisheng; et al. (Frontiers in Endocrinology, 2024)
Background Research has shown that gonadal hormones are involved in metabolic pathways relevant to metabolic syndrome (MetS). Nevertheless, no longitudinal study has been conducted on the association between SHBG and MetS in Chinese. The objective of our study was to determine whether there is any association between middle-aged and elderly males in China. Methods A total of 531 eligible male subjects, aged above 40 years or older, without MetS at baseline, were recruited. Sex hormone binding globulin (SHBG), total testosterone (TT), follicle-stimulating hormone (FSH), and luteinizing hormone (LH) were measured. A harmonized definition and recommended thresholds for the Chinese population were used to determine metabolic syndrome. Results During 3.2 years of follow-up, 20.7% of subjects had developed MetS. Compared with the non-MetS group, subjects in the new-onset MetS group had significantly lower SHBG (43.5 nmol/L [28.8, 74.9] vs 53.7nmol/L [33.8, 115.0], P=0.0018), TT (18.1nmol/L [13.6–21.7] vs 19.5nmol/L[15.0–23.6], P=0.0204), and LH (5.13mIU/L [3.63–7.29] vs 5.87mIU/L [4.05–8.36]) at baseline. The incidence of MetS was decreased according to elevated SHBG quartiles (Q1:26.9%, Q2:22.7%, Q3:21.1%, Q4:12.1%, P for trend =0.0035), TT (Q1: 25.2%, Q2:23.7%, Q3: 17.3%, Q4: 16.7%, P for trend=0.0425), and LH (Q1:25.0%, Q2:21.8%, Q3: 21.8%, Q4: 14.3%, P for trend=0.0411). Compared with those in quartile 4, the OR[CI] of incident MetS for participants in Quartile 1 was 2.33[1.13–4.79] after multiple adjustments. But associations between incident MetS and different quartiles of LH, TT, and FSH were not observed after multiple adjustments. In the subgroup analyses, the significant association between SHBG level and Mets was detected in subjects over 60 years or older, with normal BMI, without insulin resistance, and with eGFR ≥90 mL/min per 1.73m2. Conclusion Compared with TT, LH, and FSH, a lower level of SHBG is significantly related to the incidence of MetS among middle-aged and elderly males in China.